An Asymptomatic and Overelongated Styloid Process. (26th January 2017) - Soylu, Emrah; Altan, Ahmet; Sekerci, Ahmet Ercan; Akbulut, Nıhat
Abstract : Elongation of the styloid process is a rare condition. Only 4% of patients have clinical symptoms where elongated styloid process (ESP) occasionally irritates or disrupts adjacent anatomical structures, which is called Eagle syndrome. This present report was aimed at reporting an asymptomatic ESP with unusual width and length.